2014
DOI: 10.1007/s12088-014-0476-6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilizing Bacillus megaterium mj1212 Regulates Endogenous Plant Carbohydrates and Amino Acids Contents to Promote Mustard Plant Growth

Abstract: The current study was conducted to explore the potential of a phosphate solubilizing soil bacterium, Bacillus megaterium mj1212 for enhancing the growth of mustard plants. The newly isolated bacterial strain mj1212 was identified as B. megaterium using phylogenetic analysis and, its phosphate solubilization ability was shown by the clear zone formation on National Botanical Research Institute's Phosphate medium. Moreover, the phosphate solubilization ability of B. megaterium mj1212 was enhanced by optimal cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
113
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 20 publications
9
113
0
2
Order By: Relevance
“…The plant growth promotion activity of B. subtilis was significant due to enhancement in the accumulation of sugars, proline and free amino acids, which are considered as the key osmolytes for maintaining the cellular water content to protect the structures and functions of cellular organelles (Ahanger and Agarwal 2017). In a previous report, it is suggested that the association of B. megaterium increased the plant growth by stimulating the synthesis of sucrose, glucose, fructose and several amino acids (Kang et al 2014). The sugars, proline and amino acids accumulation involve as antioxidants for neutralizing the toxic ROS under stress conditions, which is leading to maintain the structure of proteins and membranes (Hayat et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The plant growth promotion activity of B. subtilis was significant due to enhancement in the accumulation of sugars, proline and free amino acids, which are considered as the key osmolytes for maintaining the cellular water content to protect the structures and functions of cellular organelles (Ahanger and Agarwal 2017). In a previous report, it is suggested that the association of B. megaterium increased the plant growth by stimulating the synthesis of sucrose, glucose, fructose and several amino acids (Kang et al 2014). The sugars, proline and amino acids accumulation involve as antioxidants for neutralizing the toxic ROS under stress conditions, which is leading to maintain the structure of proteins and membranes (Hayat et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Bacillus species occur ubiquitously in soil and produce a vast array of biologically active metabolites, such as indole acetic acid and gibberellin, in addition to solubilizing the organic phosphate that helps to increase plant growth (Kang et al 2014). Pavlo et al (2011) studied the role of microorganisms on plant growth and inhibition of disease causing pathogens; they demonstrated that the stimulation of rapid plant growth results in a failure to develop disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A numbers of bacteria promote plant growth by nitrogen fixation in rhizosphere [4]. Phosphate solubilizing bacteria which hydrolyze organic and inorganic phosphorus from insoluble compounds help to enhance the plant growth [5]. Phytohormones such as auxin, cytokinin, gibberellin produced by bacteria expressed a positive effect on plant growth [4].…”
Section: Introductionmentioning
confidence: 99%